2016
DOI: 10.1108/jfc-03-2014-0012
|View full text |Cite
|
Sign up to set email alerts
|

Stocks’ prices manipulation around national elections?

Abstract: Purpose The purpose of this paper is to examine the influence of major non-economic events such as the results of five Greek national Parliamentary elections during 1996-2009 on the Greek banks’ stocks. Design/methodology/approach Using daily data from the Athens Stock Exchange, event study methodology and market model, the results of this paper claim that the five Greek national Parliamentary elections during the 1996-2009 period had no statistically significant effect on the Greek banks’ stocks. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
6
0
2
Order By: Relevance
“…A wide range of studies (Bialkowski et al , 2008; Iyengar et al , 2017; Liew and Rowland, 2016; Sajid Nazir et al , 2014; Repousis, 2016) highlighted the effect of elections on stock price returns of firms.…”
Section: Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…A wide range of studies (Bialkowski et al , 2008; Iyengar et al , 2017; Liew and Rowland, 2016; Sajid Nazir et al , 2014; Repousis, 2016) highlighted the effect of elections on stock price returns of firms.…”
Section: Literaturementioning
confidence: 99%
“…Repousis (2016) used event study methodology to investigate Greece stocks behavior around the parliamentary election and found an insignificant effect on stock returns. Ahmed (2017) and Sajid Nazir et al (2014) found a significant effect of political events on stock market performance.…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Kenaikan FFR pada tanggal 26 September 2018 yang telah diprediksi dengan baik oleh pasar menyebabkan peristiwa tersebut tidak lagi relevan sebagai dasar pengambilan keputusan investasi pada periode peristiwa yang dibuktikan dengan tidak adanya signifikansi average abnormal return di sekitar periode peristiwa. Hasil ini didukung oleh beberapa penelitian terdahulu diantaranya Prameswari & Wirakusuma (2018), Cahyaningdyah & Cahyasani (2017), Yuniarthi (2016), Repousis (2016), serta (Lucia et. al.…”
Section: Tabel 4 Hasil One Sample T-test Average Abnormal Return (Aaunclassified
“…Affuso and Lahtinen (2019), Cwynar et al (2019), Rosati et al (2019), Strauss and Smith (2019), Teti et al (2019). While searching for bibliographic records, the stock price manipulation appears to be dealt with various facets in the market such as trading frequency (Viljoen et al , 2015), trading volume (Huang and Cheng, 2015; Adams et al , 2018), the magnitude of stock price volatility (Punniyamoorthy and Thoppan, 2013; Zhai et al , 2018; Griffith et al , 2019), abnormal returns; order size (Jiang et al , 2013; Huang and Cheng, 2015; Repousis, 2016; Shi et al , 2018), Bid-Ask Spread (Hillion and Suominen, 2004; Aitken et al , 2005; Wang and Zhou, 2014; Chan et al , 2018) and also the closing prices (Kadioglu et al , 2015; Saputra and Prijadi, 2017; Cordi et al , 2018; Davies, 2018).…”
Section: Introductionmentioning
confidence: 99%